Soybean grown after green manures under no-tillage and conventional management systems in savannah soil - Carvalho, MAC de; Athayde, MLF; Soratto, R. P.; Alves, M. C.; Arf, O. (Empresa Brasil Pesq Agropec, 2004)
The green manures aim to preserve the environment quality without discarding the largest yield of economic crops. The objective of this work was to evaluate the performance of soybean grown after green manures under no-tillage and conventional tillage (one disk harrow two leveling harrow) systems. The experiment was carried out in a Distrophic Red Latossol (typic Hapludox), covered by savannah vegetation. in Selviria, MS. Brazil. The green manures utilized were: black velvet bean, pigeon pea, sunn hemp, millet and fallow area (spontaneous vegetation). The green manures previously grown in spring do not affect the soybean yield, in both no-tillage and conventional tillage systems. In year without dry periods, the conventional tillage provided greater grain yield.
Keywords: Glycine max; sequential cropping; organic fertilizers; soil management